Investigating the use of formant frequencies in listener judgments of speaker size. (March 2016) - Barreda, Santiago
Abstract: The formant-pattern present in a given vowel sound will be determined by the vocal-tract length (VTL) of the speaker as well as by phoneme-specific information. Although human listeners tend to associate lower formant-frequencies with larger speakers, it is unclear whether they are responding to VTL information in speech sounds, or simply responding to the formant-pattern present in the sound. In this experiment listeners were presented with pairs of synthetic vowels from the set of (/i æ ʊ/), which could differ on the basis of simulated VTL and vowel category, within-pair. Listeners were divided into groups based on the number of formants contained by stimulus vowels (2, 3, 4, and 5-formant vowel groups). For each trial, listeners were asked to indicate which vowel sounded like it had been produced by a taller speaker. Results indicate that listeners do not rely solely on VTL cues when making speaker-size judgments, and that they exhibit biases towards selecting given phonemes as taller, even when contrary to the VTL differences between the voices. Furthermore, the higher formants (up to F 5) are used by listeners when making speaker-size judgments, though not in a manner consistent with VTL-based speaker-size judgments. Highlights: Apparent speaker-height is not stable across vowel phonemes, within-speaker. Height judgments are not based solely on speaker vocal-tract length estimates. Formants up to F 5 are used in the determination of speaker height.